Dielectric Properties of TiO2/Silicone Rubber Micro- and Nanocomposites - F. Madidi; G. Momen; M. Farzaneh (Advances in Materials Science and Engineering)
Room temperature vulcanized (RTV) silicone rubber SR/TiO2 nanocomposites and microcomposites are developed and characterized, and their dielectric behaviour and electrical conductivity are studied in this paper. We demonstrate that the surfactant Triton X-100 greatly improves the dispersal of micro- and nanoparticles across the surface to produce more homogeneous composites that have improved dielectric properties. This heightened dispersal with the presence of a surfactant is also confirmed by SEM analysis. We also discuss the influence of the filler concentration and particle size on the dielectric behaviour of the nanocomposites and the microcomposite surfaces having a frequency range of 40 Hz to 2 MHz. The dielectric properties are improved by the introduction of 5 wt.% and 10 wt.% TiO2 nano- and microparticles. Furthermore, there is an improvement in the permittivity values for the microcomposites compared to the nanocomposites for all frequencies. This finding is of great importance for high-voltage electrical insulation.